Effects of Eight Weeks of TRX and CXWORX Exercises on Trunk Muscle Strength, Core Endurance, and Dynamic Balance of Female College Students - Razieh Kiani; Hooman Fattahi (Shahid Beheshti University of Medical Sciences, 2021)
Background and Aims: Core stability and strengthening core stability muscles have become one of the new topics in the field of sports medicine. The present study aims to compare the effects of eight weeks of TRX and CXWORX exercises on core endurance, trunk muscle strength, and dynamic balance of female college students. Methods: This quasi-experiment study was conducted on 30 young healthy female college students. They were randomly divided into two experimental groups of TRX (n=10), CXWORX (n=10) and one control group (n=10). In the pre-test phase, trunk muscle strength was evaluated by sit-up test, dynamic balance by Y-balance test, and core endurance by McGill core endurance test. Then, experimental groups performed eight weeks of selected training program, 3 sessions per week, while the control group was asked to do their daily activities. After intervention, the three groups underwent post-test assessments. Shapiro-Wilk test was used to investigate the normality of data distribution, and repeated measured ANOVA was used to compare data. The significance level was set at P≤0.05. Results: Both TRX and CXWORX had a positive effect on the participants' trunk muscle strength, core endurance, and dynamic balance such that their mean scores increased after training. The TRX group performed better than the CXWORX group in all study variables (P≤0.05), except for the Y balance at the anterior direction. Conclusion: Both TRX and CXWORX exercises have positive effects on the trunk muscle strength, core endurance, and dynamic balance of female college students, where the effect of TRX was greater. Therefore, occupational therapists and trainers are recommended to use both exercises, especially TRX to improve core muscle strength and endurance.